Purposeful Stakeholder Engagement for Improved Environmental Flow Outcomes - Mussehl, Meghan L.; Horne, Avril C.; Webb, J. Angus; Poff, N. LeRoy (Frontiers in Environmental Science, 2022)
Rivers are dynamic social-ecological systems that support societies and ecosystems in a multitude of ways, giving rise to a variety of user groups and competing interests. Environmental flows (e-flows) programs developed to protect riverine environments are often conceived by water managers and researchers. This is despite continued calls for increased public participation to include local communities and Indigenous peoples in the development process. Failure to do so undermines social legitimacy and program effectiveness. In this paper, we describe how adaptive management of e-flows allows an opportunity to incorporate a diversity of stakeholder views through an iterative process. However, to achieve this, stakeholder engagement must be intentionally integrated into the adaptive management cycle. Stakeholder engagement in e-flows allows for the creation of a shared understanding of a river and opens collaborative and innovative management strategies that address multiple axes of uncertainty. Here, we describe a holistic framework that unifies current participatory engagement attempts and existing technical methods into a complete strategy. The framework identifies the primary steps in an e-flows adaptive management cycle, describes potential roles of various stakeholders, and proposes potential engagement tools. Restructuring e-flows methods to adequately include stakeholders requires a shift from being driven by deliverables, such as reports and flow recommendations, to focusing on people-oriented outcomes, such as continuous learning and fostering relationships. While our work has been placed in the context of e-flows, the intentional integration of stakeholder engagement in adaptive management is pertinent to natural resources management generally.